Is higher education mobility a good investment for EU lagging regions? The case of Master and Back, an active labour market policy co-financed by the European Social Fund - Enrico Orrù (European Regional Science Association (ERSA), 2012)
This research claims that investing European Union (EU) Structural Funds in Learning Mobility (LM) might lead to further regional polarization. LM is a type of labour mobility finalized to acquire new knowledge (human capital) and social networks (social capital). Historically, LM has been supported by space neutral policies, like the ERASMUS programme. However, after the mid-tem review of the Lisbon strategy (2005), also Cohesion Policy started to invest in LM and today it is considered an important priority by 1/3 of European Social Fund national programming documents (EU, 2010i). This, even though there is no evidence of LM being consistent with the historical objective of Cohesion Policy: real convergence (Molle, 2007). Human capital theory predicts investment in education to improve labour market outputs. However, when it comes to lagging regions this might not be the case both because of brain drain (Becker, 1964) and because of their inefficient labour markets (Rodríguez-Pose and Vilalta-Bufí, 2005) . In order to shed light on these issues, this paper relies on a case study: the programme Master and Back (M&B). M&B is an early example of Structural Funds devoted to learning mobility and has been carried out since 2005 by the Italian region Sardinia. It consists of financing young Sardinian residents endowed with excellent CVs to take masters and PhDs in the best world universities and then of facilitating their return by means of economic incentives. In order to evaluate the impact of the programme, the labour market outputs of the recipients have been compared to those of a suitable control group by means of Propensity Score Matching (Rosenbaum and Rubin, 1983). In particular, the following outputs have been considered: odds of employment, earnings and odds of emigration. Both administrative data and web survey data have been collected. Overall 207 treated units and 1,201 control units have participated to the survey, corresponding respectively to 50% and 20% of response rate. The results show that M&B has had no significant effect neither on odds of employment nor on earnings, while it seems to have increased the odds of emigration. These findings imply that lagging regions should be very careful when investing in learning mobility and that EU Cohesion Policy should pay more attention to the risks of further regional polarization.
Keywords: 330